Digital Image Processing - Jähne, Bernd (Springer Berlin Heidelberg, 2005)
Foundation -- Applications and Tools -- Image Representation -- Random Variables and Fields -- Neighborhood Operations -- Multiscale Representation -- Image Formation and Preprocessing -- Quantitative Visualization -- Image Formation -- 3-D Imaging -- Digitization, Sampling, Quantization -- Pixel Processing -- Feature Extraction -- Averaging -- Edges -- Simple Neighborhoods -- Motion -- Texture -- Image Analysis -- Segmentation -- Regularization and Modeling -- Morphology -- Shape Presentation and Analysis -- Classification.
Gesehen am 19.04.2017
Keywords: Bildverarbeitung